Tatapan Medusa dan Okularsentrisme: Budaya Visual dan Persoalan Sinema Kontemporer - Bawono, Haryo Tejo (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2020)
This article presents some fundamental matters in visual culture. Philosophy has been grappling with important issues of image and ocularcentrism. These matters have shaped and brought impacts on the world’s visual culture. On the one hand, an image with all its possible interpretations today tends to be captured as an object and not so much as something that is at the same time plural and moving. On the other hand, people’s way of seeing tends to be blurred by the ocularcentrism. This might be a crucial problem that brings significant implications on one of the most important aspects of human life, that is, art activity, and particularly on cinema. The author of this article invites the readers to be aware of the negative inclinations around the issues of image and ocularcentrism. Some of the important challenges in the cinematic world are how people continually reformulate their experience of an image and how the ocularcentrism character in our visual culture can be positioned in the heart of the matter. In an effort to respond to these challenges, one can approach philosophy in a different way in order to refresh his or her way of seeing that might have been tiresome and cloudy.